Financial risk management a practitioner's guide to managing market and credit risk + website - Allen, Steven, 1945- (Hoboken, N.J. : John Wiley & Sons, 2012)
This book offers an insider's view of this discipline and covers the strategies, principles, and measurement techniques necessary to manage and measure financial risk.
Foreword -- Preface -- Acknowledgments -- Introduction -- Institutional background -- Operational risk -- Financial disasters -- The systemic disaster of 2007-2008 -- Managing financial risk -- Var and stress testing -- Model risk -- Managing spot risk -- Managing forward risk -- Managing vanilla options risk -- Managing exotic options risk -- Credit risk -- Counterparty credit risk -- Bibliography -- About the companion website -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Financial risk management; Finance; BUSINESS & ECONOMICS -- Insurance -- Risk Assessment & Management; Finance; Financial risk management; Electronic books